Biodeterioration of mortar coating in historical buildings: Microclimatic characterization, material, and fungal community. (15th May 2019) - Guerra, Fernanda L.; Lopes, William; Cazarolli, Juciana C.; Lobato, Mariane; Masuero, Angela B.; Dal Molin, Denise C.C.; Bento, Fátima M.; Schrank, Augusto; Vainstein, Marilene H.
Abstract: The estimation of climate conditions and different moisture sources associated with the substrate composition and features in historical buildings is crucial to evaluate the substrate biodeterioration by filamentous fungi. Knowing the main agents and their frequency in substrates is relevant to propose conservation approaches focused on buildings preservation. Therefore, the mineralogic composition characterization of the historic building mortar coatings in Porto Alegre, RS was performed by binder/aggregate proportioning, x-ray diffraction, x-ray fluorescence, and thermogravimetric analyses. The microclimate conditions of indoor environments were evaluated through relative humidity (RH) and temperature recording sensors measurements. The qualitative and quantitative identification of filamentous fungi from the mortar coating was performed by microculture and DNA extraction for PCR and molecular analysis. The analyses indicated a mortar coating predominated by CaCO3 and MgCO3 with quartz sand and traces ratio between 1:2 and 1:5.4. The indoor microclimate had mean RH above 70% and a mean temperature above 20°C most of the time. Approximately 60 colonies of fungi were isolated, and 13 isolates were identified as the most frequent ones; among them: Aspergillus niger, Cladosporium sphaerospermum, Cladosporium spp ., Purpureocillium lillacinus, Lecanicillium spp., Trichoderma atroviride, and T. harzianum . Highlights: The correlation between the indoor microclimate and fungal deterioration in a historical building was evaluated. Different moisture sources influenced the fungal diversity and frequency. The correlation between the mineralogical composition of historical mortars and fungal growth was estimated. The fungal molecular identification was performed considering the substrate and regional constraints.